Hirschsprung Disease in an Infant with L1 syndrome: Report of a New Case and a novel L1CAM variant. Issue 3 (4th February 2021) - Gauntner, Timothy D.; Karumuri, Manasa; Guzman, Miguel A.; Starnes, Sara E.; Besmer, Sherri; Pinz, Hailey; Braddock, Stephen R.; Andreone, Teresa L.
Abstract: L1syndrome is an X‐linked disorder manifesting with congenital hydrocephalus, adducted thumbs and spasticity. There are rare cases of L1 syndrome and coincident Hirschsprung disease, with mutations in the L1CAM gene thought to underlie both. We present a novel pathogenic L1CAM variant in someone with L1 syndrome and Hirschsprung disease. Abstract : L1syndrome is an X‐linked disorder manifesting with congenital hydrocephalus, adducted thumbs and spasticity. There are rare cases of L1 syndrome and coincident Hirschsprung disease, with mutations in the L1CAM gene thought to underlie both. We present a novel pathogenic L1CAM variant in someone with L1 syndrome and Hirschsprung disease.